A New Way to Separate Anions and Cations (Global Journal of Science Frontier Research, 2020)
Electrolysis is currently widely used for the production of various substances, as well as for the isolation of individual elements from the composition of chemical compounds, which by electrolysis are decomposed into anions and cations. For this purpose, electrolysis of aqueous solutions is used, which makes it possible to carry out such a separation in a simple way. For this, electrolyzers are used, where a current is passed through aqueous solutions, while the anions are grouped near the cathode, and the cations are near the anode, from where they are taken. The article considers a new method for the separation of anions and cations, which is based on the polarization of electrolytes. This method differs from the known ones in that it does not require passing current through the electrolyte, which reduces the cost of the production process.
Keywords: electrolysis; electrolyzer; anion; cation; caustic; chlorine